KEKUATAN TEKAN MATERIAL SPOILER MOBIL BERBASIS KOMPOSIT ROTAN EPOKSI - Agustinus Purna Irawan (Program Studi Teknik Mesin Universitas Tarumanagara, 2018)
This study aims to obtain the compressive strength of the material of a car spoiler product that was developed using materials from rattan fiber epoxy reinforced composites material. The car spoiler products are car accessories that also function as one of the equipment related to aerodynamics. The study was conducted by making test samples of rattan fiber epoxy reinforced composites and compared with the compressive strength of plastic spoiler materials obtained from the free market. The testing standard used is the compressive strength test of ASTM D 695. Based on the test results obtained compressive strength of spoiler made of plastic is 47.68 ± 1.37 MPa and rattan fiber epoxy reinforced composites material is 43.49 ± 4.21 MPa, with a compressive strength difference of 8.8%. The compressive strength of modeling results obtained a compressive strength of 47.97 MPa. This result is quite good and the difference is quite small, so the results of the study can be used as a reference for further product development.